2014
DOI: 10.3390/ijms15046925
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Resveratrol against IL-1β-Induced Inflammatory Response on Human Osteoarthritic Chondrocytes Partly via the TLR4/MyD88/NF-κB Signaling Pathway: An “in Vitro Study”

Abstract: Resveratrol is a natural polyphenolic compound that prevents inflammation in chondrocytes and animal models of osteoarthritis (OA) via yet to be defined mechanisms. The purpose of this study was to determine whether the protective effect of resveratrol on IL-1β-induced human articular chondrocytes was associated with the TLR4/MyD88/NF-κB signaling pathway by incubating human articular chondrocytes (harvested from osteoarthritis patients) with IL-1β before treatment with resveratrol. Cell viability was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 44 publications
(47 reference statements)
2
52
0
Order By: Relevance
“…IL‐1β also induces the production of the inflammatory mediators, NO and PGE 2 that play critical roles in the development of OA [Chen et al, ]. Therefore, inhibition of IL‐1β‐induced MMPs and inflammatory mediator production would be beneficial in the treatment of OA [Liu et al, ]. In this study, the production of MMP‐1, MMP‐3, and MMP‐13 was upregulated in SW1353 cells after the stimulation by IL‐1β.…”
Section: Discussionmentioning
confidence: 64%
“…IL‐1β also induces the production of the inflammatory mediators, NO and PGE 2 that play critical roles in the development of OA [Chen et al, ]. Therefore, inhibition of IL‐1β‐induced MMPs and inflammatory mediator production would be beneficial in the treatment of OA [Liu et al, ]. In this study, the production of MMP‐1, MMP‐3, and MMP‐13 was upregulated in SW1353 cells after the stimulation by IL‐1β.…”
Section: Discussionmentioning
confidence: 64%
“…Resveratrol, examined in previous studies, may prevent the progression of OA through several different mechanisms [166-168]. Interestingly, resveratrol modulates the expression of a number of miRNAs involved in inflammation and disease progressio that including miR-663, miR-155, and miR-2 [169-171].…”
Section: Current and Future Therapiesmentioning
confidence: 99%
“…Its presence results in attenuation of the potential repair of articular cartilage [Goldring et al, ] by up‐regulating the expression of MMP‐3, MMP‐9, and MMP‐13, which degrade the cartilage matrix [Klatt et al, ]. Inhibition of IL‐1β‐induced MMP and inflammatory mediator production is useful in the treatment of OA [Liu et al, ]. In this study, the production of MMP‐3, MMP‐9, and MMP‐13 was increased in chondrocytes after stimulation by IL‐1β.…”
Section: Discussionmentioning
confidence: 64%
“…To control the progression of the OA, pharmacological and dietary methods have been used [Kaneva et al, ; Xu et al, ]. Previous studies have showed that natural products might be useful for the treatment of OA and rheumatoid arthritis [Kang et al, ; Liu et al, ; Moon et al, ]. CoQ10, an endogenous antioxidant, can suppress the IL‐1β‐induced inflammatory response in some diseases [Fuller et al, ; Schmelzer et al, ].…”
Section: Discussionmentioning
confidence: 99%